2011
DOI: 10.1097/nna.0b013e3182171aff
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Manager Leadership Development

Abstract: The complexities of healthcare demand new leadership approaches to achieve organizational goals while developing and sustaining healthy work environments. The nurse manager is the defining role, crucial to achievement of workplace outcomes. Preparing nurses for this dynamic, complex role is often dependent on didactic education or on-the-job training that falls short of true leadership development. The authors describe an innovative approach to the development of successful nursing leaders across an integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 16 publications
0
56
0
Order By: Relevance
“…This study LOPES ET AL. 527 F I G U R E 1 The hypothesized seven-factor model (column 1) and five models' candidate (columns [2][3][4][5][6] found that PHC managers in Timor-Leste are not competent in problem solving on financial management in their jobs. The finding was similar to the studies conducted in South Africa 40 and Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study LOPES ET AL. 527 F I G U R E 1 The hypothesized seven-factor model (column 1) and five models' candidate (columns [2][3][4][5][6] found that PHC managers in Timor-Leste are not competent in problem solving on financial management in their jobs. The finding was similar to the studies conducted in South Africa 40 and Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…47 The introduction of changes in the organization's management, staff, and services showed the need for new management competencies. 5,48 Furthermore, the organization requires competent managers to make an organization successful. 49 Any organized health program's success depends on effective management.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Often nurse managers are selected for their position, based on their clinical expertise, without the proper preparation to manage people, coordinate units, considering the budget and using the technology in their daily lives [22].…”
Section: Discussionmentioning
confidence: 99%
“…11 Focusing on the development of TL skills among FLNMs is an imperative for nurse executives in supporting clinical, leadership, and organizational success. [12][13][14] Evidence demonstrates that independent of knowledge and skill, there are organizational and work design factors that promote or impede transformational behaviors among leaders. 3,4,11 As the healthcare environment is redesigned to meet the challenges of access, quality, and value, FLNMs are pivotal in helping to change the environments of acute care hospitals.…”
mentioning
confidence: 98%